Biofilms as a sink for antibiotic resistance genes (ARGs) in the Yangtze Estuary. (1st February 2018) - Guo, Xing-pan; Yang, Yi; Lu, Da-pei; Niu, Zuo-shun; Feng, Jing-nan; Chen, Yu-ru; Tou, Fei-yun; Garner, Emily; Xu, Jiang; Liu, Min; Hochella, Michael F.
Abstract: Biofilms are ubiquitous throughout aquatic environments and they are thought to promote the acquisition and dissemination of antibiotic resistant genes (ARGs). This study focused on the occurrence and distribution of five types of ARG in naturally-occurring biofilms, in comparison to associated sediment and water samples, from the Yangtze Estuary, which borders the meta-city of Shanghai, China. The detection frequency and abundances of most ARGs showed the following order: biofilm > sediment > water, which can be attributed to a high level of antibiotics and metals that can accelerate the generation and propagation of ARGs in biofilms. Most of ARG abundances were contributed by extracellular DNA (eDNA) in biofilm and sediment samples. ARGs ( sul 1, sul 2, tet A and tet W) in eDNA were significantly correlated with TOC in both biofilm and sediment samples. Furthermore, both intracellular DNA-associated ARGs per gram of microbial biomass carbon (MBC) and eDNA-associated ARGs per gram of non-MBC and were higher in biofilms than sediments, and the partitioning coefficients of ARGs in eDNA between biofilm and water were higher than those between sediment and water. Our results provide new insight for evaluating the occurrence and abundance of ARGs in aquatic environments, confirming that biofilms are a significant sink for ARGs in the estuarine environment. Graphical abstract: Highlights: Most of ARG abundances in the Yangtze Estuary showed: biofilm > sediment > water. Antibiotics, metals, TOC and bacterial density may regulate ARGs in biofilms. Most of ARGs were contributed by extracellular DNA in both biofilms and sediments. Biofilm/water partitioning coefficients of ARGs in eDNA were higher than those of sediment/water.